WHAT CAN “WHY I LEFT BUZZFEED” VLOGS TEACH US ABOUT INVISIBLE LABOUR? - Bergstrom, Kelly (AoIR Selected Papers of Internet Research, 2018)
In this paper I explore the growing trend of posting videos to YouTube to explain the reasons for why an individual has quit their job, detailing a collection of 10 vlogs posted by 11 former BuzzFeed employees to explain their reasons for leaving the company. I argue that the vlogs made by ex-employees are a deliberate attempt to expose the invisible labour that is prevalent in the post-Internet media industry. By posting “Why I Left” vlogs, former employees reclaim their authorship of creative productions previously uploaded without individual attributions and instead credited to the faceless corporate monolith of “BuzzFeed”. Furthermore, these vlogs act as a means to subvert notoriety earned by being a (now former) public face of BuzzFeed to attract hundreds of thousands, if not millions, of viewers to announce their personal pivot and rebranding as content producers now working independently from the company that had launched them into Internet fame. While perhaps not intentional, these vlogs ultimately act as a warning about the uneven playing field between employer and employee. Each year BuzzFeed posts record profits, and yet these vlogs illuminate how employees are actively prevented from being able to grow a personal brand beyond BuzzFeed, stifling future career prospects and additional sources of income. Ultimately this leaves BuzzFeed employees with the option to quit or to stagnate in place, or what Gaby Dunn (2015) stated are ultimately the two options for a BuzzFeed viral video star: “Get Rich, or Die Vlogging.’”